Assistance in The Implementation of Innovative Islamic Religious Education Learning Models for Teachers - Tohet, Moch; Rodmaya, Ramanda Satria; Homaidi, Homaidi (Communautaire: Journal of Community Service, 2025)
This paper aims to improve the competence of teachers in implementing the innovative Islamic Religious Education learning model at madrasas. The background of this activity is based on the findings that PAI teachers in the madrasah still use many conventional lecture methods, have limitations in designing innovative learning tools, and have not received training or assistance in applying active, collaborative, and contextual learning approaches. Therefore, this activity is designed to provide intensive training and mentoring to introduce innovative learning models and their applications in the classroom. The activity was carried out for six weeks and involved various parties, including the PKM team, madrasah heads, expert resource persons, and PAI teachers as the main participants. The success of the program is measured through increasing teachers' understanding of innovative learning models, the ability to prepare contextual lesson plans, and significant changes in the implementation of learning that are more active, interesting, and touch the affective realm of students. The final results of the activity show that this assistance has a positive impact on the quality of PAI learning, both in terms of process and student learning outcomes. This activity is expected to be a model for empowering teachers in developing religious learning that is relevant to the challenges of 21st century education.